Efek Histopatologis Insektisida λ-Cyhalothrin terhadap Insang, Hati, dan Usus Halus Ikan Nila (Oreochromis niloticus L., 1758) - Siwi Dwi Rahayu; Zeyna Listy Zulfatin; Ardaning Nuriliani (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
λ-cyhalothrin is phyrethroid insecticide that can pollute the waters environment and cause sublethal as well as lethal effects to non-target organisms such as tilapia. This research were aimed to study the LC50 96 h value and histopathological effects of λ-cyhalothrin on the gills, liver, and small intestine of tilapia. In this research fish were divided into control group and the treatment groups of λ-cyhalothrin at the concentration of 3, 6, 9, and 12 µg/L. The treatment used a static system for 96 hours. The LC50 96 h value was analyzed by linear regression. Histopathological effects on the organs were analyzed using descriptive comparative. Histological preparation was done by the paraffin method, fixed in Bouin solution, and stained with Hematoxylin-Eosin. The results showed that LC50-96 h values of λ-cyhalothrin on tilapia was 6.519 µg/L. Gills damages were in the form of hyperplasia, necrosis, edema, secondary lamella fusion, removal of lamella epithelial cells, and primary lamella dilatation. Liver damages include hemorrhage, intravascular hemolysis on blood vessels, piknosis, and leukocytes infiltration. The intestine damages were fatty degeneration, edema, leukocyte infiltration, hemorhage, cloudy swelling, vacuolisation, necrosis, and arthropy. The gills, liver, and small intestine damages of tilapia range from slight to severe. It could be concluded that λ-cyhalothrin caused histopathological effects on the gills, liver, and small intestine of tilapia.